The Role of Social and Humanitarian Cooperation in the Development of Russian-Georgian Relations - Mansurov, Timur Zufarovich; Ivanov, Radmir Vladimirovich (International Journal of Criminology and Sociology, 2022)
The study is aimed at detection of the features of social and humanitarian cooperation between Russia and Georgia and their impact on the development of relations between the two countries. The possibilities of implementing this cooperation are considered in the absence of political and diplomatic relations. The authors analyze the specifics of inter-state ties and relations development in social, cultural, scientific, educational and spiritual spheres, as well as the obstacles that hinder such interaction. The potential of inter-state dialogue formats such as the "Geneva discussions on security and stability in Transcaucasia", as well as the "Karasin-Abashidze" diplomatic line is being studied. Special attention is paid to the role of non-profit organizations and foundations, including those operating on the territory of Georgia, contributing to the expansion of contacts and ties between the two countries and promotion of the Eurasian vector of Georgia’s development. Based on the empirical data of sociological research conducted both in Russia and Georgia, the author of the article identifies the problems that exist in the relations between the two states, and shows the importance of deepening social and humanitarian cooperation to solve them. Research data shows that currently the number of supporters of the pro-Russian vector of the country development, which can become a significant factor in solving many social, economic and political problems of the Georgian state.